Evaluating the Impact of a Structured Teaching Program on the Knowledge of Mothers with Children Under Five Regarding Upper Respiratory Tract Infections and Home Remedies in a Selected Primary Healthcare Area in Bengaluru - Ramamani A.; Manjunatha H.R. (International Journal of Emergency and Trauma Nursing and Practices, 2023)
Background: Upper Respiratory Tract Infections are contagious infections involving the nose, throat sinuses, pharynx, larynx, tonsils, and adenoids. The typical upper respiratory tract infections are nasopharyngitis (common cold), tonsillitis, sinusitis, laryngitis, and pharyngitis etc., Precautionary measures in early stages can help to prevent complications. Further, home remedies can offer comfort from symptoms and reduce the duration of illness and these home remedies have no side effects, but also boost up the immune system. These home-remedies are best and suitable even for children below 5 years of age, so, mothers should have the adequate knowledge regarding these simple home remedies. Objectives: The research aimed to assess the impact of a structured teaching program on the awareness of mothers with children under the age of 5 years regarding upper respiratory tract infections and home remedies for such infections. Materials and Methods: The study was undertaken by using one group pre-test and post-test design, a Quantitative research approach, 60 mothers of under-fives were included in the study. Data was gathered through an interview schedule, and subsequent analysis employed both descriptive and inferential statistics. The results were subsequently displayed using tables and graphs. Results: The results depicted that the overall post-test mean knowledge score among the respondents was found to be 78.88% with a SD of 2.01 compared to the overall pre-test mean knowledge score of 49.76% with a SD of 1.95. The results of the study indicated that the structured teaching program successfully enhanced understanding of home remedies for upper respiratory tract infections in children. This is corroborated by a paired 't' value of 52.16, exceeding the critical table value (2.00) at a significance level of 0.05 for all facets investigated in the study.
Keywords: Knowledge; effectiveness; mothers of under-fives; structured teaching programme and home remedies